Back Cover Maharot Vol. 6, No. 1, Januari – Juni (2022) - Back Cover Maharot Vol. 6, No. 1, Januari – Juni (2022) (Institut Dirosat Islamiyah Al-Amien Prenduan, 2022)
Back Cover Maharot Vol. 6, No. 1, Januari – Juni (2022)